Histological diagnostic criterion for chronic endometritis based on the clinical outcome - Hirata, Kimiko (BMC Womens Health, 2021)
BACKGROUND: The diagnostic criteria of chronic endometritis remain controversial in the treatment for infertile patients. METHODS: A prospective observational study was conducted in a single university from June 2014 to September 2017. Patients who underwent single frozen-thawed blastocyst transfer with a hormone replacement cycle after histological examination for the presence of chronic endometritis were enrolled. Four criteria were used to define chronic endometritis according to the number of plasma cells in the same group of patients: 1 or more (≥ 1) plasma cells, 2 or more (≥ 2), 3 or more (≥ 3), or 5 or more (≥ 5) in 10 high-power fields. Pregnancy rates, live birth rates, and miscarriage rates of the non-chronic endometritis and the chronic endometritis groups defined with each criterion were calculated. A logistic regression analysis was performed for live births using eight explanatory variables (seven infertility factors and chronic endometritis). A receiver operating characteristic curve was drawn and the optimal cut-off value was calculated. RESULTS: A total of 69 patients were registered and 53 patients were finally analyzed after exclusion. When the diagnostic criterion was designated as the presence of ≥ 1 plasma cell in the endometrial stroma per 10 high-power fields, the pregnancy rate, live birth rate, and miscarriage rate were 63.0% vs. 30.8%, 51.9% vs. 7.7%, and 17.7% vs. 75% in the non-chronic and chronic endometritis groups, respectively. This criterion resulted in the highest pregnancy and live birth rates among the non-chronic endometritis and the smallest P values for the pregnancy rates, live birth rates, and miscarriage rates between the non-chronic and chronic endometritis groups. In the logistic regression analysis, chronic endometritis was an explanatory variable negatively affecting the objective variable of live birth only when chronic endometritis was diagnosed with ≥ 1 or ≥ 2 plasma cells per 10 high-power fields. The optimal cut-off value was obtained when one or more plasma cells were found in 10 high-power fields (sensitivity 87.5%, specificity 64.9%). CONCLUSIONS: Chronic endometritis should be diagnosed as the presence of ≥ 1 plasma cells in 10 high-power fields. According to this diagnostic criterion, chronic endometritis adversely affected the pregnancy rate and the live birth rate.